Operation Characteristics and Security Control Measures of UHV Loop Network with Multi-Hierarchical DC Infeed after Breaking - Shuaitao BAI; Dezhi CHEN; Shiying MA; Qing DONG; Wei TANG; Ping JI; Cheng YANG; Xikai JIANG (Zhongguo dianli)
The operation of a provincial UHV AC loop network provides conditions for hierarchical access and full power accommodation of multiple UHV DC systems, and also increases the coupling strength between UHV AC and UHV DC, and between 1000 kV/500 kV AC power grids at the receiving end. To ensure the reliable operation of UHV AC/DC power grids after line fault occurs, simulation is used to analyze the voltage stability characteristics of the coupled AC and DC systems after breaking of the 1000 kV UHV loop network, and the thermal stability characteristics of the power system when large power transfers to the 500 kV power grid after breaking, and the causes for voltage stability and thermo-stability problems are studied. In order to reduce the amount of security control measures, a unified multi-resource co-control optimization model is established for controlling the two operational problems, with consideration of the sensitivity and priority of multiple control methods such as DC modulation and load shedding. And a control-cost-based heuristic optimization method of constant-step gradient descent is proposed to obtain the co-control measures. It is verified through simulation of an actual power grid that the proposed controlling method can effectively reduce the amount of prevention and control measures.